Provider Commitment Is Key for High Vaginal Birth After Cesarean Delivery Rate in a Community Hospital [274]. (May 2015) - Follette, Lizellen La; Lo, Alyssa; Koblentz, Jenna; Main, Elliott Kingwill
Abstract : INTRODUCTION: As a community hospital committed to vaginal birth after cesarean delivery (VBAC), we reviewed our experience from 2000 to 2013 to identify contributors to successful VBAC. Our health care providers were both midwives and physicians. METHODS: Using an electronic clinical database that served as a partial electronic medical record, we reviewed records from 2000 to 2013 for all women who had a prior cesarean delivery. We collected patient demographics, insurance, epidural use, and health care provider type. All labor trials were examined for details of labor management, indication for and dilation at cesarean delivery, and neonatal morbidities. Although we reviewed all VBACs in the final analysis, we excluded women who had had a prior vaginal birth. The analysis was then confined to women who had had one prior birth that was via cesarean section. RESULTS: A total of 1, 788 women with a single prior birth that was a cesarean delivery were studied, among whom 617 had a VBAC attempt (34.5%); 431 VBAC attempts were successful (70%). Among 289 VBAC attempts among private patients (epidural rate of 73%), the success rate was 66%. For 328 MediCal public patients (epidural rate of 50%), the success rate was 73%. Neither maternal age at delivery nor maternal BMI prior to gestation influenced VBAC success rates. However, private patients were approximately 7 years older than the public patients (mean private age of 36 years old with a standard deviation of 4 years versus the mean public age of 29 years old with a standard deviation of 5 years). Private patients also had a lower pregestation BMI than the public patients (private BMI of 24 versus public BMI of 27 with a standard deviation of 5). Due to changes in county funding in 2011, a combined public and private foundation model was established and a hospitalist care model for labor and delivery was expanded. Although public patients remained primarily managed by midwives as they had been in the past, now private foundation patients had access to both the midwives and hospitalists that may be different from their prenatal doctor. All other variables remained the same, namely, in house 24/7 anesthesia and pediatrics along with in-house OB (as the hospitalist) and in-house midwife. As this collaborative model progressed from 2011 to 2013, we were able to see a reversal of decreasing VBAC rates combined with continued high VBAC success along with good maternal and neonatal safety profiles. Among private patients, the VBAC rate starting at 19% in 2010 (had been as low as 12% in 2007), ended up at a high of 33% in 2013. In addition, neonatal outcomes among VBAC attempt patients were excellent with a single uterine rupture (0.2%) and a 5-minute Apgar less than 7 rate of 0.4%, both unchanged from the earlier period. CONCLUSION: Despite calls for more VBACs, a 10% VBAC rate nationally has not budged much in the last 5 years. Within the same small community hospital (1500 births/year), among all health care provider groups, VBAC rates started high, then followed the descending national rates and then in 2011 reversed. This reversal was due to an increase in VBAC attempts and largely related to a new collaborative model in which private doctors allowed other providers to manage and deliver their patients. Those providers could be either the in-house midwife or the OB hospitalist. In addition, the VBAC success rate was uniformly high at 70%. Health care provider commitment is critical to achieving higher VBAC rates in hospitals that offer VBAC. In this setting, VBAC was quite safe.